The Relationship Between Micro-Counseling Skills and Clinical Attendance - Wolstein, Dan Aaron (East Carolina University, 2014)
Project Working Recovery (PWR) was a clinic that operated at East Carolina University in the Addictions and Rehabilitation Studies Department from April 2008 until June 2009. Intake procedures were followed and clients who were eligible participated in counseling services. The counseling sessions were recorded with audio and video data (clients were left off-screen). The current study sought to use this archival data to investigate the relationship between micro-counseling skills used in the first session with clients, and clinical attendance. The way counselors responded to clients was coded into micro-counseling skills using the Motivational Interviewing Treatment Integrity (MITI). Two coders were trained to use the MITI, via a 2-week training period using sample videos for coding. A convenience sample of videos collected during PWR was used; data was analyzed for 88 clients total. A multiple regression was run to analyze the relationship between micro-counseling skills and clinical attendance.   Another multiple regression was run to analyze the relationship between problem severity and clinical attendance. The current study utilized results of the Addiction Severity Index (ASI), which was administered upon intake of participants, to determine whether problem severity had an impact on clinical attendance. One research question and five hypotheses were developed. The results of the multiple regression analysis were not significant for the research question or any of the five hypotheses. The results of the first multiple regression suggest that the way that counselors respond to clients in this study does not promote nor deter clients from utilizing services. The results of the second multiple regression suggest that the level of problem severity does not influence clinical attendance for the clients in this study. The limitations of the study are detailed and rationale is given as to why these limitations may have affected the findings of the study. Implications for the field of counseling are discussed and recommendations for future research are made.
Keywords: Counseling psychology; Attendance; Micro-counseling; MITI; Counseling; Patient Compliance; Motivational Interviewing